STUDI ANALISIS TERHADAP KINERJA BADAN AMIL ZAKAT (BAZ) KOTA BOGOR DALAM MENINGKATKAN JUMLAH USAHA PRODUKTIF PARA MUSTAHIQ - Apriansyah, Arif (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2011)
Since 2006, BAZ Bogor has stared a business that helps mustahiq to expand its business. Shaped in the form of revolving capital and business guidance, so that poor families can finally do its business independently and productively, and slowly delivers them in a more decent life, and eventually their status can be changed to Muzakki. If the mandate can be implemented by the Amil Zakat as one of the city of Bogor in Indonesia LPZ, undoubtedly can help alleviate or at least can reduce poverty.